Chronic active Epstein–Barr virus infection mimicking tuberculosis – A diagnostic enigma - Shilpi Thakur; Manish Soneja; Deepam Pushpam; Saumyaranjan Mallick (Indian Journal of Pathology and Microbiology)
Chronic active EBV infection is a rare disorder prone for misdiagnosis. They present with a wide range of symptoms from indolent to aggressive clinical course. Clinico-pathological correlation with confirmation by ancillary techniques is inevitable to diagnose this disease. We present a case of a 29-year-old male with fever, weight loss, and lymphadenopathy for 6 months. Lymph node biopsy showed occasional granuloma with preserved architecture. Suspected to have tuberculosis, he received antitubercular treatment (ATT) with no response for 3 months. Subsequently, additional workup showed many EBV-positive cells in sinusoids with high serum EBV titer, confirming the difficult diagnosis of CAEBV. The present case highlights the difficulty in the diagnosis of this entity and also emphasizes the necessity to recognize this disorder in countries endemic for tuberculosis, as it is no longer bound by ethnicity and geographical boundaries.